MEASURING AND ANALYZING THE IMPACT OF FINANCIAL SUSTAINABILITY INDICATORS ON IRAQ'S TRADE BALANCE FOR THE PERIOD 2010-2023 (World Economics and Finance Bulletin, 2026)
The President of the General Union of the Gulf Chambers of Commerce presented the objectives of the Gulf Chambers Federation. It examines how the development on trade balance is influenced by key public finance indicators such as public debt to GDP ratio, tax pendant, and budget deficit or it’s surplus. An improvement in the indicators of fiscal sustainability is expected to get improved the performance of the trade balance through strengthening stabilization and diminishing structural asymmetries. The study applied analytical and econometric rules by utilizing official annual data of the Iraqi statistical agencies. Econometric models were employed to yield the nature and strength of the relationship between the variables and the impact. Findings indicate major effects of financial sustainability indicators on the trade balance through the analysis of data. The study’s conclusion suggests that enhancing financial sustainability through revenue diversification, rationalization of public expenditure, and debt management are factors that enhance the trade balance and stabilize Iraq’s economy
Keywords: Public debt to GDP ratio; tax gap; primary surplus or deficit